2021
DOI: 10.1021/acs.chemmater.1c00267
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystalline Metallic Films Induced by van der Waals Epitaxy on Black Phosphorus

Abstract: The properties of metal-semiconductor junctions are often unpredictable because of non-ideal interfacial structures, such as interfacial defects or chemical reactions introduced at junctions. Black phosphorus (BP), an elemental two-dimensional (2D) semiconducting crystal, possesses the puckered atomic structure with high chemical reactivity, and the establishment of a realistic atomic-scale picture of BP's interface toward metallic contact has remained elusive. Here we examine the interfacial structures and pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…Its physical properties strongly depend on its crystal lattice direction. Phosphorene exhibits strong anisotropic in-plane charge transport behavior and one-dimensional diffusion on its surface. , Although ZZ terminations are the predominant configurations in phosphorene, its edges have not been observed at the atomic level to a significant degree. In particular, it is difficult to image phosphorene edges because they are degraded by ambient exposure and unintended alterations to them during characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Its physical properties strongly depend on its crystal lattice direction. Phosphorene exhibits strong anisotropic in-plane charge transport behavior and one-dimensional diffusion on its surface. , Although ZZ terminations are the predominant configurations in phosphorene, its edges have not been observed at the atomic level to a significant degree. In particular, it is difficult to image phosphorene edges because they are degraded by ambient exposure and unintended alterations to them during characterization.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, Wang et al (2014 ) prepared the BP–Ti thin film and BP–carbon nanotube hybrid and innovatively demonstrated that BP can well drive the oxygen evolution reaction (OER). For the van der Waals layered structure of BP, the exfoliation and thickness reduction could not only effectively improve the electrical transport performance but also increase the number of active sites and improve the OER performance of BP ( Huang et al, 2019 ; Lee et al, 2021 ). Ren et al ( Ren et al, 2017 ) prepared the few-layered BP nanosheets by liquid-phase exfoliation and found that the OER onset-potential and Tafel slope of BP nanosheets were achieved at 1.45 V and 88 mV dec −1 .…”
Section: Introductionmentioning
confidence: 99%